THE ROLE OF INTERPERSONAL CAPITAL IN SHAPING THE PROFESSIONALISM OF INDONESIAN AIR FORCE PERSONNEL - Anton Pallaguna (MANAGER: Journal of Management and Administration Science, 2025)
The increasingly complex and dynamic security environment has intensified the demand for professionalism among military personnel, including those of the Indonesian Air Force (TNI AU). While military professionalism has traditionally been associated with technical competence and operational readiness, recent developments indicate that interpersonal capabilities play a critical role in shaping professional conduct. This study aims to examine the role of interpersonal capital as a foundational element of professionalism among TNI AU personnel. This research employs a qualitative descriptive approach to explore how interpersonal capital—comprising leadership, trust, integrity (amanah), teamwork, and interpersonal communication—contributes to the development of military professionalism. Data were collected through semi-structured interviews with personnel and officials involved in education, training, and human resource development within the TNI AU, complemented by document analysis of relevant policies, training guidelines, and institutional reports. The data were analyzed using qualitative techniques involving data reduction, thematic presentation, and inductive conclusion drawing, with source triangulation applied to ensure data credibility. The findings reveal that interpersonal capital plays a significant role in shaping professionalism among TNI AU personnel. Leadership emerges as the most influential element, functioning as a primary channel for transmitting professional values and norms. Trust and integrity foster responsibility, internal discipline, and commitment beyond formal supervision, while effective teamwork and interpersonal communication enhance coordination, cohesion, and operational effectiveness. The study also finds that interpersonal values have been implicitly embedded in the education and training system of the TNI AU, although their effectiveness remains highly dependent on leadership example and organizational culture. This study concludes that interpersonal capital constitutes a fundamental pillar of military professionalism. Strengthening interpersonal capital through more structured and systematic integration into education and training programs is therefore essential for fostering sustainable professionalism and enhancing organizational effectiveness within the Indonesian Air Force.